CARE OF ASSISTED LIVING RESIDENTS APPROACHING END OF LIFE: A PROCESS OF NEGOTIATING RISKS. (11th November 2018) - Perkins, M; Vandenberg, A; Ball, M; Kemp, C; Bender, A
Abstract: Foundational research shows that some older adults coping with chronic illness and decline are particularly resilient. However, we know little about how resilience operates in various vulnerable subgroups of older adults, such as racial/ethnic minorities or those who are coping with illnesses that may carry a social stigma (e.g., dementia or HIV). Understanding these nuances will become increasingly important as the aging population becomes more diverse. This study builds on theory from 20 years of research conducted in diverse assisted living (AL) settings in Georgia to focus on the resilience process among residents approaching end of life (EOL). Data used in the current analysis are from a 5-year NIA-funded grounded theory study (5R01AG047408) that includes 2, 645 hours of observation and in-depth interviews with 73 residents and 88 care providers (e.g., families, hospice). Residents are diverse in race and socioeconomic status and have a mean age of 86. They are coping with 7 chronic conditions (e.g., dementia, HIV, diabetes) on average and exhibit substantial frailty and cognitive impairment. Many experience physical as well as social, psychological, and spiritual pain. Findings show that residents' ability to maintain a positive sense of self and minimize suffering hinges on a process we label "negotiating risks." This process involves a complex interplay of social determinants at multiple social ecological levels. Access to social capital, including "weak ties" forged among residents, is a key protective factor. Findings have implications for individual and facility-level interventions that can reduce suffering and promote resilience among AL residents at EOL.